(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Dark Triad can potentially predict monetary attitudes; however, the literacy in students’ monetary attitudes is still limited. Objective: To study the roles of mediating variables among students’ monetary attitudes that were influenced possibly by saving, spending and indifference attitudes according to Sereetrakul (2014) with the human Dark Triad personality: Machiavellianism, Narcissism, and Psychopathy. Methods: Cross-sectional was methodologically designed with randomly selected 310 Thai university students. Saving Behavior Scale and Short Dark Triad Thai Version (SD3-TH) were provided through the online platform in their computer classrooms. The T-test indicated the significant differences in mean scores. The indirect effect of simple mediation and multiple mediation models were examined. The Sobel test and Bootstrapping 95% confident interval were verified under Hayes’ PROCESS method judgement. Results: Loan students showed significantly higher in all 3 monetary attitudes and higher in Machiavellianism and Narcissism than self-support students. Female showed higher significantly in Psychopathy than male. Presence of mediator appeared on Machiavellianism that could predict both positive saving and spending attitude outcomes. Conclusions: This study highlighted the presence of mediators that potentially explained a new definition which the higher saving higher monetary indifference attitudes as the satisfied point between saving and spending attitudes in Machiavellianism and Narcissism personality groups.